PENGEMBANGAN APLIKASI GAME IQRO’ SEBAGAI MEDIA EDUKASI PADA ANAK MENGGUNAKAN CONSTRUCT 2 - Marnini Marnini; Nurhasan Nugroho; Ahmad Munawir (Computer Based Information System Journal, 2025)
Learning to read the Qur’an is a fundamental component of early Islamic education, with the Iqro’ method being one of the most widely used approaches in Indonesia. However, traditional implementations often lack interactivity and engagement, which can reduce their appeal to young learners. In response to this challenge and the increasing digital exposure among children, this study aims to develop an educational game application using Construct 2 as a supplementary medium for teaching Iqro’ reading skills to first-grade students at SD IT Al-Jauharotunnaqiyah Ciajeng. The application presents material from Iqro’ Volume 1 in an interactive format, incorporating audio pronunciation, multiple-choice quizzes, writing simulations, and immediate visual and auditory feedback. The implementation results indicate that the application fulfills both functional and non-functional requirements. Furthermore, black-box testing confirms that all features perform as intended. This application is considered a suitable and engaging tool to support early Qur’anic literacy and has the potential to redirect children’s screen time toward educational and spiritually enriching activities.